Domestic tourist destination satisfaction: a case of Kuala Selangor - Mohamed Zakaria, Hasan; Aziz, Azlizam (Global Academic Excellence, 2018)
This present study attempts to determine the satisfaction of visitors from the importance and ability of attractiveness attribute. From the importance and ability assigned by the visitor, an IPA analysis was conducted. A survey has been conducted between May to June 2017 in multiple attraction sites in Kuala Selangor. A total of 390 responses were analysed using SPSS software programme. The result finds that heritage, history and cultural attraction is the only attractiveness attribute that satisfied visitor. In conclusion, these findings will provide additional knowledge on how domestic visitor perceived the attraction in Kuala Selangor in term of satisfaction and which attribute need to be focused by destination marketers for future marketing strategy.